Pengembangan Media Pembelajaran Flashcard Augmented Reality Berbasis Aplikasi Assemblr Edu untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VI di SDN 6 Sila - Nur Bunaya; Abdul Kadir Jaelani; Ibrahim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low critical thinking ability of students is a significant problem in science learning in elementary schools, especially because learning is still dominated by conventional methods and the use of less interactive media. This condition results in a lack of active student involvement in understanding concepts in depth. Therefore, media innovations are needed that are able to integrate concrete visualization and interactivity. This study developed an Augmented Reality Flashcard media based on the Assemblr Edu application that not only emphasizes the feasibility aspect, but also tests the effectiveness of its use in learning. This study aims to determine the validity, practicality, and effectiveness of the Augmented Reality Flashcard learning media based on the Assemblr Edu Application to improve the critical thinking skills of sixth grade students at SDN 6 Sila. This research method uses the ADDIE development method consisting of five stages including analysis, design, development, implementation, and evaluation. The validation results of material experts obtained a score of 92%, and media experts obtained a score of 94% in the very valid category. The results of the student response questionnaire were 92.61%, and the teacher response was 85.45% in the very practical category. The results of the students' pretest and posttest using the N-Gain calculation obtained an N-Gain value of 0.66, which is in the moderate category, indicating an increase in students' critical thinking skills. Thus, it can be concluded that the augmented reality flashcard learning media is very valid, very practical, and effective.